A Seminar on the Teaching of Accounting. - Williams, Doyle Z. (The Accounting Review, 1966)
Abstract The article focuses on conducting a seminar on college and university accounting teaching in order to increase the teaching competence of fresh graduates. A report of the American Accounting Association's 1964 committee on teacher development suggested such an approach to improve the teaching of accounting. The proposed seminar would do more than train accounting teachers in the mechanics of teaching. It would introduce the doctoral candidate to some of the problems and rewards of college teaching; explain the role of higher education in society; examine the learning process; consider the problems of students; relate the approaches of effective teaching to testing and measuring performance; introduce the current issues in accounting education and curriculum development; and take a look at accounting education of the future. It is believed that this seminar, if properly handled, will not only help to improve the classroom performance of a new accounting teacher but will also make him acquainted with some of the significant issues of accounting education.